Design of Financial Management Talent Training Model under Demand Coupling Mechanism and IoT Applications - Guo, Ying (Wireless communications and mobile computing, 2022)
The financial environment of businesses and institutions has significantly changed due to the development of new technologies and the deepening of vocational education reform. The Financial Management Department is, in theory, responsible for the financial management of the company. Specialty benefits from both the accounting and finance specialties. The advanced stage of corporate financial activity management is cash-related management. As a result, the social demand subject should praise graduates of the financial management specialty. The subject of social demand is also a good motivation to raise proficient capacity necessities for graduates. Regardless, there is a huge hole among organic market for proficient capacity under the current ability preparing model, in light of the fact that numerous schools and colleges that set monetary administration claims to fame are uncertain of the expert capacity necessities of the social interest subject, monetary in nature. Graduates in executive positions are in a more humiliating position on the job market. In light of this, this paper proposes the basic idea of talent training model innovation in the financial management specialty, based on an analysis of the status and causes of professional ability supply and demand. The board specialises in determining talent training goals, revising professional talent training programs, respecting the central status of students, and engaging in innovative teaching activities. Using Sichuan University of Arts and Science as an example, this paper examines the current state of practice teaching of financial management in colleges and universities, incorporates course practice content into the national vocational and technical certificate, promotes the integration of professional courses and vocational qualification certificates, discusses the new mode of practice instructing of university-enterprise cooperation, and makes recommendations. With the quick movement of the economy and society, the force of science and innovation, similarly as steady getting the hang of; perception; and usage of the significance of data and capacity progression has never been more prominent. Schools are the establishment for propelling one’s capacities. China as of now has an enormous number of colleges, showing that 100 blossoms are growing and 100 distinct perspectives are contending. Each school has its own unmistakable character and attributes. Regardless, the mirror of market economy obviously mirrors the condition of the economy contamination, commitment, bad behaviors, and veritable financial discipline encroachment of endless high-situating insightful individuals, addressing a real test to school capacity improvement.